KARATERISTIK RESILIENSI PADA PASIEN HIV DI KABUPATEN KARO - Friska Ginting (Elisabeth Health Jurnal, 2019)
Human Immuno deficiency Virus (HIV) is a disease that requires an bio-psychosocio- spiritual approach. The life of an HIV sufferer is very dependent on the surrounding environment. The most dominant influence on HIV sufferers is healthy behavioral, psychological and physical functions of others' ability to be able to accept the attitudes and behavior of others to support the social life of HIV sufferers. Viewed from the sex, women are more vulnerable and more sensitive in accepting the conditions they suffer. HIV has become a pandemic that causes world anxiety. Individuals who suffer from HIV positive with high resilience will have more enthusiasm for life. Method: This type of research is an analytic survey research using descriptive design that aims to identify resilience in HIV sufferers. The population in this study were 90 people with HIV diagnoses, both men and women in Karo District, while the sample for this study was based on sample criteria. Results: The results obtained from the frequency distribution table showed that the majority of HIV sufferers' work history were 18 people (58.0%), 11 drivers (35.5) and 2 (6) housewives (IRT) 5%). Based on the sex of the female as many as 20 people (64.5%) and the male sex as many as 11 people (35,%), from the age of the patients found 25-35 years as many as 25 people (80.6%), aged 36-45 years as many as 5 people (16.1%) and ≥ 46 years old as many as 1 person (3.3%). And the highest level of education is at the high school level of 25 people (54.3%). Conclusion: Based on the results of the study, it is recommended that HIV sufferers consult more often about physical and psychological conditions at the nearest health center.